Lactobacillus acidophilus NCFM and Lactiplantibacillus plantarum Lp-115 inhibit Helicobacter pylori colonization and gastric inflammation in a murine model - Shen, Siqi; Ren, FeiFei; Qin, Haiming; Bukhari, Ihtisham; Yang, Jing; Gao, Dafang; Ouwehand, Arthur C.; Lehtinen, Markus J.; Zheng, Pengyuan; Mi, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose To determine the role of Lactobacillus strains and their combinations in inhibiting the colonization of H. pylori and gastric mucosa inflammation. Methods Human gastric adenocarcinoma AGS cells were incubated with H. pylori and six probiotic strains (Lactobacillus acidophilus NCFM, L. acidophilus La-14, Lactiplantibacillus plantarum Lp-115, Lacticaseibacillus paracasei Lpc-37, Lacticaseibacillus rhamnosus Lr-32, and L. rhamnosus GG) and the adhesion ability of H. pylori in different combinations was evaluated by fluorescence microscopy and urease activity assay. Male C57BL/6 mice were randomly divided into five groups (uninfected, H. pylori, H. pylori+NCFM, H. pylori+Lp-115, and H. pylori+NCFM+Lp-115) and treated with two lactobacilli strains (NCFM and Lp-115) for six weeks. H. pylori colonization and tissue inflammation statuses were determined by rapid urease test, Hematoxylin-Eosin (HE) staining, immunohistochemistry, and qRT-PCR and ELISA. Results L. acidophilus NCFM, L. acidophilus La-14, L. plantarum Lp-115, L. paracasei Lpc-37, L. rhamnosus Lr-32, and L. rhamnosus GG reduced H. pylori adhesion and inflammation caused by H. pylori infection in AGS cells and mice. Among all probiotics L. acidophilus NCFM and L. plantarum, Lp-115 showed significant effects on the H. pylori eradication and reduction of inflammation in-vitro and in-vivo. Compared with the H. pylori infection group, the mRNA and protein expression levels of IL-8 and TNF-α in the six Lactobacillus intervention groups were significantly reduced. The changes in the urease activity (ureA and ureB) for 1-7h in each group showed that L. acidophilus NCFM, L. acidophilus La-14, L. plantarum Lp-115, and L. rhamnosus GG effectively reduced the colonization of H. pylori. We observed a higher ratio of lymphocyte and plasma cell infiltration into the lamina propria of the gastric mucosa and neutrophil infiltration in H. pylori+NCFM+Lp-115 mice. The infiltration of inflammatory cells in lamina propria of the gastric mucosa was reduced in the H. pylori+NCFM+Lp-115 group. Additionally, the expression of IFN-γ was decreased significantly in the NCFM and Lp-115 treated C57BL/6 mice. Conclusions L. acidophilus NCFM and L. plantarum Lp-115 can reduce the adhesion of H. pylori and inhibit the gastric inflammatory response caused by H. pylori infection.